PERAN PEREMPUAN DALAM KEGIATAN PARIWISATA DI KAMPUNG WISATA TEBING TINGGI OKURA KOTA PEKANBARU - Andani, Faradilla; ", Musadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Tebing tnggi okura village is one of the tourist village area of pekanbaru city that has a vision to realize the improvement of local community welfare, according to prority the role of local communities, especially the role of women. The role of women is important in a tourism activity because the role of women in tourism can reduce inequal gender inequality, therefore this research (1) to find out how the rule of women in tourism activities in tebing tinggi okura tourist village (2) to find out what are the constraints of women in playing a role in tourism activities in tebing tinggi okura tourist village. This research design using qualitative method with descriptive approach, which researchers will take data from informants who know clearly about women’s participation in tourism activities in tebing tinggi okura tourist village at pekanbaru city.The results showed that the position of women in the tourist village of okura is very important, especially in the component of tourism activities offered in the tourist village of okura. The constraints of women in playing a role in tourism activities in tebing tinggi okura tourist village in is lack of funding sources, cultural limitations, lack of expertise, and lack of trained human resourcesKeywords : The Role of Women, The Tourism Component, The Tourist Village Of Tebing Tinggi Okura, Pekanbaru City